2010
DOI: 10.1007/s11103-010-9610-y
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-driven plasticity in growth cessation and dormancy development in deciduous woody plants: a working hypothesis suggesting how molecular and cellular function is affected by temperature during dormancy induction

Abstract: The role of temperature during dormancy development is being reconsidered as more research emerges demonstrating that temperature can significantly influence growth cessation and dormancy development in woody plants. However, there are seemingly contradictory responses to warm and low temperature in the literature. This research/review paper aims to address this contradiction. The impact of temperature was examined in four poplar clones and two dogwood ecotypes with contrasting dormancy induction patterns. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(152 citation statements)
references
References 74 publications
9
141
0
2
Order By: Relevance
“…The timing of bud-set closely follows the cessation of primary shoot growth (Gyllenstrand et al 2007;Rohde et al 2011). It is often assumed that the autumnal cessation of primary meristem activity and bud-set are fully controlled by the photoperiod (detected by the phytochrome receptor) in the majority of temperate tree species (Tanino et al 2010;Way 2011). However, recent experimental studies have demonstrated that temperature additionally modulates the timing of bud-set and the cessation of primary growth in a number of temperate and boreal tree species (e.g., Salminen and Jalkanen 2007), with both temperature and photoperiod acting in an interactive, non-monotonous manner (Rohde et al 2011;Heide 2011).…”
Section: Phenology Of Leaves and Reproductive Structuresmentioning
confidence: 99%
“…The timing of bud-set closely follows the cessation of primary shoot growth (Gyllenstrand et al 2007;Rohde et al 2011). It is often assumed that the autumnal cessation of primary meristem activity and bud-set are fully controlled by the photoperiod (detected by the phytochrome receptor) in the majority of temperate tree species (Tanino et al 2010;Way 2011). However, recent experimental studies have demonstrated that temperature additionally modulates the timing of bud-set and the cessation of primary growth in a number of temperate and boreal tree species (e.g., Salminen and Jalkanen 2007), with both temperature and photoperiod acting in an interactive, non-monotonous manner (Rohde et al 2011;Heide 2011).…”
Section: Phenology Of Leaves and Reproductive Structuresmentioning
confidence: 99%
“…However, we must keep in mind that programmed genetic systems of bud dormancy regulation may not necessarily be the same among the diverse plant species that exhibit bud dormancy, even though most perennial woody plants have adapted and evolved dormancy for survival. In addition, primary environmental cues that trigger the bud phenology cycle, such as the induction of bud set (or shoot tip abortion), vary depending on a given plant species (Tanino et al, 2010). Accordingly, the characterization of molecular networks regulating the dormancy of various woody species is being carried out by omics studies that use the target plants themselves.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a recent study showed that smaller temperature increments (+1.5°C to +3°C) applied using infrared heaters did not delay down-regulation of photosynthesis or impair freezing tolerance in field-grown P. strobus seedlings that were acclimated to larger diurnal and seasonal temperature variations . For many tree species, photoperiod determines cessation of growth (Tanino et al, 2010;Petterle et al, 2013), length of the growing season (Bauerle et al, 2012), and development of cold hardiness (Welling et al, 1997;Li et al, 2003;Rostad et al, 2006). However, the effects of climate warming on tree phenology are complex and can be unpredictable due to species-and provenancespecific differences in sensitivity to photoperiod and temperature cues (Körner and Basler, 2010;Basler and Körner, 2012;Basler and Körner, 2014).…”
mentioning
confidence: 99%